How common knowledge is constructed and why it matters in collaboration between professionals and clients. (2017) - Hopwood, Nick; Edwards, Anne
Highlights: Reveals how profession-client collaboration on complex problems is accomplished. Focus on socially significant education services for families with children at-risk. Extends cultural-historical conceptualisation of partnership work. Connects different approaches to analysis for first time. Explains crucial and problematic features of professional-client work. Abstract: Professionals are increasingly called upon to work with clients. We employ cultural-historical concepts to reveal how professionals and clients accomplish joint work on problems in services for families with young children. Professional–client interactions in day stay and home visiting services are considered, first focusing on how matters of concern are worked into departures of significance (employing 'D-analysis'), then conceptualising joint professional–parent work in terms of common knowledge and the object of activity. The importance of motives and their alignment is revealed. We show the value of D-analysis in elucidating how common knowledge can be constructed and why this process may be problematic. Finally, we reflect on the fluid and situated nature of this kind of collaborative work.